2017
DOI: 10.3390/fluids2020015
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Optimization of Colebrook’s Turbulent Flow Friction Approximations

Abstract: This paper presents evolutionary optimization of explicit approximations of the empirical Colebrook's equation that is used for the calculation of the turbulent friction factor (λ), i.e., for the calculation of turbulent hydraulic resistance in hydraulically smooth and rough pipes including the transient zone between them. The empirical Colebrook's equation relates the unknown flow friction factor (λ) with the known Reynolds number (R) and the known relative roughness of the inner pipe surface (ε/D). It is imp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
69
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4
1

Relationship

5
5

Authors

Journals

citations
Cited by 40 publications
(69 citation statements)
references
References 54 publications
0
69
0
Order By: Relevance
“…The here presented unified flow friction approach is flexible, as proposed equations for certain hydraulic flow regime can be easily changed. Although our previous experiences with artificial intelligence [38][39][40] showed that encapsulation of all flow friction regimes into a one coherent model is not a straightforward task, the here proposed form is simple. Thus, the here presented unified approach can be easily implemented in software codes.…”
Section: Discussionmentioning
confidence: 99%
“…The here presented unified flow friction approach is flexible, as proposed equations for certain hydraulic flow regime can be easily changed. Although our previous experiences with artificial intelligence [38][39][40] showed that encapsulation of all flow friction regimes into a one coherent model is not a straightforward task, the here proposed form is simple. Thus, the here presented unified approach can be easily implemented in software codes.…”
Section: Discussionmentioning
confidence: 99%
“…We used [computer software] Eureqa by Nutonian, Inc., Boston, MA, as a genetic programming tool [22,23]. The symbolic regression approach adopted herein [24][25][26][27][28][29] is based upon genetic programming wherein a population of functions is allowed to breed and mutate with the genetic propagation into subsequent generations based upon a survival-of-the-fittest criteria [30]. The main goal of this study is to make accurate and computationally cheap explicit approximations of the Colebrook equation, where computationally cheap means to contain the least possible number of logarithmic functions and non-integer powers [31][32][33][34][35][36].…”
Section: Methods Used Preparation Of Data and Software Tool Resultsmentioning
confidence: 99%
“…Usually, with the initial guess that is close to the exact solution, the iterative procedure converges to it in five or fewer iterations. (Brkić 2017). Here the goal is to avoid use of logarithmic functions and therefore, this starting point is not suitable.…”
Section: Initial Starting Point For the Proposed Iterative Methodsmentioning
confidence: 99%